Natural hydrocarbon seepage on the continental slope to the east of Mississippi Canyon in the northern Gulf of Mexico. (17th June 2013) - Rahman Talukder, Asrarur; Ross, Andrew; Crooke, Emma; Stalvies, Charlotte; Trefry, Christine; Qi, Xiubin; Fuentes, David; Armand, Stephane; Revill, Andrew; ,
Abstract [1] From 5 June to 15 September 2010, a multidisciplinary marine survey was undertaken onboard the M/V Ryan Chouest in the region of the BP Deepwater Horizon incident site in the Gulf of Mexico. The primary objective of the survey was the continuous monitoring of hydrocarbon abundance from sea surface down to a maximum depth of 120 m. Compound abundances were inferred using a hydrocarbon sensor array with associated vertical cast system. In order to better understand the potential inputs from natural seepage in the vicinity of the spill, a Simrad EK60 high‐resolution split beam echo sounder, operated at 38 kHz, was included in the survey between 7 July and 15 September 2010. During this period, three fields of natural seeps characterized by hydroacoustic flares were studied in detail. These seep fields are at water depths of approximately 430 m, 880 m, and 1370 m. They are associated with extensive cold seep systems. In particular, the area around Seep Field 1 (the vicinity of Deepwater Horizon) seems to present a vast area of active natural seepages in the Gulf of Mexico. The repeat surveys at two of the fields suggested that the cold seep systems here were active, with expulsions of hydrocarbons into the water column, at least during the periods of our acoustic surveys. Multiple lines of evidence gathered during the survey indicated that the observed hydroacoustic flares at the three fields identified consisted of oily bubble streams of gases of thermogenic origin. However, direct observation and sampling are required to reveal the precise nature of the flares. In the deep water Gulf of Mexico, the formation of a hydrate rim around bubbles seems to be a very important mechanism for the long transport of methane and oil in the water column.